HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN DEMAM BERDARA DENGUE DI SEMARANG - Erna Sari; Nur Endah Wahyuningsih; Retno Murwani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue hemorrhagic fever (DHF) or dengue hemorrhagic fever (DHF) is an acute febrile illness accompanied by deep bleeding that has a tendency to cause shock or convulsions and can lead to death, generally affecting children younger than 15 but now the sufferer can come from an adult. Dengue transmission is influenced by environmental factors, both physical environment, chemical and biological. The physical environment directly affects the composition of vector species, mosquito breeding habitat, population, longevity and transmission. This study aims to find the relationship between the physical environmental factors of the house with the incidence of DHF. Using analytic observational research with case-control study design. The sample amounted to 80 consisting of 40 case samples and 40 control samples with a ratio of 1: 1. Data collection in this research using questionnaire and measurement tool that is thermohygro meter and lux meter. The results were analyzed using chi square test and odds ratio. The result showed no relationship between the presence of ventilated vents (p = 0.33) and air humidity with the occurrence of DHF (p = 0,692) and there was correlation between light intensity in house with the incidence of DBD (p = 0,001). The conclusion that can be taken is the environmental factor is very influential in supporting the mosquito breeding process, so if the environment around the house is not maintained and treated properly can increase the risk for dengue fever.